2020
DOI: 10.1101/2020.07.10.20150680
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Addition of Tocilizumab to the standard of care reduces mortality in severe COVID-19: A systematic review and meta-analysis

Abstract: Introduction: Tocilizumab is an anti-interleukin-6 antibody that has been used for the treatment of severe coronavirus disease 2019 (COVID-19). However, the concrete evidence of its benefit in reducing the mortality in severe COVID-19 is lacking. Therefore, we performed a systematic review and meta-analysis of relevant studies that compared the efficacy of Tocilizumab in severe COVID-19 vs. standard of care alone. Methods: Literature search for studies that compared Tocilizumab and Standard of care in the tr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 51 publications
1
23
0
3
Order By: Relevance
“…Eighteen studies assessed the mortality of COVID 19 patients following treatment with tocilizumab with an overall mortality rate 21% (251/1212)). The other metanalysis carried to assess efficacy of tocilizumab in case controlled and cohort studies also reported similar mortality rate of 22.4% (258/1,153) when compared to control [6]. However it is noteworthy to mention there was a substantial heterogeneity(I 2 =78.9%) in our study which is also similar to other published metanalysis (I 2 =80%) [6].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Eighteen studies assessed the mortality of COVID 19 patients following treatment with tocilizumab with an overall mortality rate 21% (251/1212)). The other metanalysis carried to assess efficacy of tocilizumab in case controlled and cohort studies also reported similar mortality rate of 22.4% (258/1,153) when compared to control [6]. However it is noteworthy to mention there was a substantial heterogeneity(I 2 =78.9%) in our study which is also similar to other published metanalysis (I 2 =80%) [6].…”
Section: Discussionsupporting
confidence: 90%
“…A characteristic feature of COVID-19 during its progression in severity is the cytokine storm (via interleukin-6, IL-6) which is responsible for secondary acute respiratory distress syndrome (ARDS) [2][3] [4]. ARDS is the most devastating complication of SARSCoV-2 with a higher death toll [5] [6]. The incidence of ARSD following COVID-19 is higher in severe cases.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence summary A meta-analysis of 3641 patients including 16 studies (13 retrospective cohort studies and 3 prospective cohort studies) showed that adding tocilizumab (TCZ) to standard of care (SOC) may reduce the mortality of severe COVID-19 (Pooled OR = 0.57, 95% CI 0.36-0.92, P = 0.02), and it did not report any adverse effect. However, this evidence body was a lowquality evidence with degrading factors: more confounding factors (the difference in the age and comorbidities, variability in the follow-up period) and significant heterogeneity (I 2 = 80%) among the included studies [78].…”
Section: Implementation Considerationsmentioning
confidence: 96%
“…The first SRMA, published by Lan SH Zhang et al [13], included 7 studies, with no conclusive evidence that TCZ would provide any additional benefit to patients with severe COVID-19. The second, registered in the medRxiv repository by Boregowda et al [14] included 16 studies, concluding that the addition of TCZ to the SOC might reduce the mortality in severe COVID-19.…”
mentioning
confidence: 99%